Constraints Faced by Women Self Help Groups Involved in Dairy Farming from Hingoli District of Maharashtra (Indian Journal of Extension Education, 2017)
The present investigation was carried out to ascertain the perceived constraints faced by women Self Help Groups. The study was carried out in Hingoli, Aundha and Basmat talukas of Hingoli district of Maharashtra with a sample size of 120 respondents with the help of well structured and pre-tested interview schedule. The data collected were subjected to statistical analysis and results were interpreted. High cost of feed, high cost of medicines / treatment, non-availability of green fodder, lack of technical guidance, less number of doctors, receiving low price of milk, high cost of high yielding breeds, non-availability of credit, lack of training programmes, higher incidences of diseases, lack of knowledge regarding vaccination and de-worming schedule, inadequate knowledge about feeding, delay in payments from dairy co-operative societies, low conception rate through A.I., lack of preservation facilities for their milk, inadequate knowledge of diseases and their prevention and control, low productivity of local breeds, distant location of milk collection centers were the major constraints faced by respondents in dairy farming.